Implikasi Pendidikan dari Q.S Al-Israa Ayat 37 tentang Sikap Sombong - Fiera Martila Safira; Aep Saepudin (UNISBA Press, 2024)
Abstract. The purpose of this research is to find out the opinions of interpretive experts, find out its essence, find out the opinions of experts about the meaning of arrogance and find out the educational implications of Q.S Al-Isra verse 37 regarding arrogant attitudes. This research uses a qualitative approach using descriptive methods. The data collection technique is a literature survey. Research activities are carried out through in-depth study of various commentaries and books related to the subject matter. To analyze the collected data, the author used the tahlili method. The work process of the Tahlili method is to interpret the meaning of the verses of the Koran. Several conclusions drawn from this research are: 1) Summary of Q.S Al-Israa verse 37, arrogant attitude which has several characteristics, namely walking while shaking or swaying the body, stretching cloth beyond the ankles, wearing excessive jewelry, unnecessary hunting and boasting about beauty or strength. 2) the essence of education Q.S Al-Israa Verse 37 Arrogance is the worst act and is hated by Allah SWT. The qualities of anger include many qualities to avoid and commands for Tawadhu. 3) Educational implications of Q.S Al-Israa Verse 37 Strengthen the values of monotheism towards Allah SWT by always drawing closer to Him, cultivating and getting used to mutual respect, mutual respect and maintaining brotherhood with others and building confidence that all the blessings that Allah gives, one must be grateful and responsible. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui pendapat para ahli tafsir, mengetahui essensinya, mengetahui pendapat para ahli tentang makna kesombongan dan mengetahui implikasi pendidikan dari Q.S Al-Isra ayat 37 tentang sikap sombong. Penelitian ini memakai pendekatan kualitatif dengan menggunakan metode deskriptif. Teknik pengumpulan datanya berupa survei literatur. Kegiatan penelitian dilakukan melalui kajian mendalam terhadap berbagai tafsir dan buku yang berkaitan dengan pokok permasalahan. Untuk menganalisis data yang terkumpul, penulis menggunakan metode tahlili. Proses kerja metode Tahlili adalah menafsirkan makna ayat-ayat Al-Quran. Beberapa kesimpulan yang diambil dari penelitian ini yaitu: 1) Rangkuman Q.S Al-Israa ayat 37 sikap sombong yang mempunyai beberapa ciri yaitu berjalan sambil menggoyangkan atau melenggokan badan, merentangkan kain melebihi mata kaki, memakai perhiasan yang berlebihan, berburu yang tidak perlu dan menyombongkan keindahan atau kekuatan. 2) essensi pendidikan Q.S Al-Israa Ayat 37 Kesombongan adalah perbuatan yang paling buruk dan sangat dibenci oleh Allah SWT. Sifat-sifat marahan mencakup banyak sifat yang harus dihindari dan perintah untuk Tawadhu. 3) Implikasi pendidikan dari Q.S Al-Israa Ayat 37 Perkuat nilai-nilai tauhid terhadap Allah SWT dengan selalu mendekatkan diri kepada-Nya, membudayakan dan membiasakan saling menghormati, saling menghargai dan menjaga persaudaraan dengan sesama dan membangun keyakinan bahwa segala nikmat yang Allah berikan, seseorang harus bersyukur dan bertanggung jawab.